The Transformation of Laghouat’s Ghouts: Altered Oasis Landscapes and the Fragmentation of Urban Identity (1985–2024) (International Journal of Environmental Sciences, 2025)
Laghouat, a mid-sized oasis city on the northern fringe of the Algerian Sahara, has historically drawn its identity from the Ghouts—traditional agro-oasis gardens where date palms and crops are cultivated in hand-dug depressions that access shallow groundwater. The city’s urban fabric has also been structured around the Oued M’zi, an intermittently flooded riverbed. This study examines urban transformations between 1985 and 2024, with the dual aim of quantifying vegetation decline and assessing its implications for urban identity, which is understood here as the interrelationships among built form, vegetation, and water systems. Multi-temporal Landsat imagery was processed through Google Earth Engine, focusing on April–May datasets to maximise phenological contrast. Vegetation dynamics were assessed using the Normalised Difference Vegetation Index (NDVI), while urban expansion was delineated through supervised classification. Morphological changes were further documented via high-resolution imagery (Google Earth, Maxar) and field observations. Results indicate that built-up areas expanded by 130.7% (+13.3 km²), whereas vegetated surfaces declined by 15.1% (−0.36 km²); overall vegetation cover fell from 23.3% to 8.6%, with green space per hectare reduced by 63%. Spatial analysis reveals a stratified urban landscape comprising the historic compact core, transitional hybrid zones, recent peripheral extensions, and institutional enclaves. These shifts have fragmented continuous tree canopies, weakened microclimatic regulation, and diminished the legibility of the city’s oasis identity. The findings underscore the urgency of integrating oasis-based criteria into planning frameworks to reconcile demographic pressures with ecological resilience in desert-edge cities.